The Effects of Hourly Rounding by Nursing Staff on Patient Safety and Satisfaction: Implications for Clinical Practice and Healthcare Administration - Alshammari, Saad Hamoud Suwayyid; Alfowais, Faisal Abdulaziz; Al-Mutairi, Mubarak Ghazi Aali; Aldhafeeri, Dhari Dghaim; Alshmmri, Faisal Ahmed; Khdhaier , Alshammari Mohammad (Journal of Ecohumanism, 2024)
Hospital admissions present significant challenges for patients and their families, often leading to feelings of vulnerability and dependence. Hourly rounding by nursing staff has emerged as a potential strategy to improve patient safety and satisfaction by proactively addressing patient needs.This systematic review evaluated 16 published studies on the impact of hourly rounding on patient satisfaction, call light usage, and patient falls. A comprehensive search was conducted in databases such as Medline, EMBASE, and CINAHL. The studies were analyzed for methodological rigor, outcomes, and applicability to clinical practice.The findings indicate that hourly rounding significantly enhances patient satisfaction and reduces call light usage, highlighting a direct correlation between proactive nursing care and improved patient perceptions of responsiveness. Units with initially low satisfaction scores experienced the most substantial improvements, emphasizing the potential benefits of implementing hourly rounding in such contexts.While the review revealed a low to moderate level of evidence regarding the efficacy of hourly rounding, the consistency of positive outcomes across multiple studies suggests that this practice can meaningfully enhance patient experiences in hospital settings. Nurse administrators are encouraged to adopt hourly rounding protocols tailored to their specific environments, acknowledging the need for further research to optimize implementation strategies.